Physical and thermodynamic characterization of the rice gibberellin receptor/gibberellin/DELLA protein complex. Issue 1 (December 2018) - Xiang, Hongyu; Okamura, Hideyasu; Kezuka, Yuichiro; Katoh, Etsuko
Abstract Gibberellins (GAs) are phytohormones that regulate various developmental processes in plants. The initial GA signalling events involve the binding of a GA to the soluble GA receptor protein GID1, followed by the binding of the complex to the negative transcriptional regulator of GA signaling, the DELLA protein. Although X-ray structures for certainArabidopsis GID1/GA/DELLA protein complexes have previously been determined, examination of these complexes did not fully clarify how a DELLA protein recognizes and binds to a GID1/GA complex. Herein, we present a study aimed at physically defining, via a combination of gel chromatography, isothermal titration calorimetry (ITC), small-angle X-ray scattering experiments (SAXS), NMR spectroscopy and mutagenesis, how the rice DELLA protein (SLR1) binds to the rice GID1/GA complex. We have identified the shortest SLR1 sequence (M28-A112) that binds the rice GID/GA complex tightly. The binding constant for the ternary complex that includes SLR1(M28-A112) is 2.9 × 107 M−1 ; the binding is enthalpically driven and does not depend on the chemical nature of the bound GA. Furthermore, the results of SAXS, ITC, and gel filtration experiments indicate that when free in solution, SLR1(M28-A112) is a natively unfolded protein. The NMR experiments expand this observation to show that the unfolded mutant also contains a small amount of marginally stable secondary structure. Conversely, the protein has a highly ordered structure when bound one-to-one to GID1/GA.